Manuscript designing and developing the form and condition for integrating the quran with acquired knowledge - Ahmad Bazli Ahmad Hilmi; Muhammad Hafiz Saleh; Adibah Sulaiman @ Mohamad; Wan Nasyrudin Wan Abdullah; Afrizal Nur (Penerbit Universiti Kebangsaan Malaysia, 2024)
Integrating Quranic verses with acquired knowledge is necessary, along with knowledge and technology development. This helps in understanding the Quranic verses that are relevant to those fields and further exploring the contents of the Quran more broadly. However, the form of integration of the Quran with aqli knowledge and the conditions for such integration based on the expert agreement have not been highlighted. This study aims to design and develop the integration of Quranic verses with acquired knowledge form and its condition based on the discipline of Quranic exegesis. The study used the three-phase Design and Development Research (DDR) approach, and this paper only discussed the second phase, design and development. The form of the integration and its condition was designed based on the literature review and Focus Group Discussion (FGD) by seven (7) experts in the related field of study. Then, the Fuzzy Delphi Method (FDM) was used to develop the form and condition. Twelve (12) experts in Quranic exegesis have participated in FDM. Experts’ consensus has been obtained in developing the forms for integrating Quranic verses with acquired knowledge and its conditions. The forms involve eleven items: Discussion of Concept, Discussion of the Quranic Approach, Explanation of function, Explanation of feature, Explanation of process, Explanation of cause and effect, Rational explanation of aspects of language, Explanation of Islamic legislation’s wisdom, Explanation of historiography and geography of the stories in the Quran, Inspirational Innovation by the Quran, Translational Technology from the Quran. The conditions for integrating consist of nine items and the experts emphasise the conditions concerning ethics more than the conditions relating to interpretation content. This study has significant implications for using new methods, namely design and development research. This study also contributes to the Quranic studies itself using quantitative and qualitative studies that combine various methods in one study.